PVDF Fibers Modification by Nitrate Salts Doping - Sobola, Dinara; Kaspar, Pavel; Částková, Klára; Dallaev, Rashid; Papež, Nikola; Sedlák, Petr; Trčka, Tomáš; Orudzhev, Farid; Kaštyl, Jaroslav; Weiser, Adam; Knápek, Alexandr; Holcman, Vladimír (Polymers, 2021)
The method of inclusion of various additives into a polymer depends highly on the material in question and the desired effect. In the case of this paper, nitride salts were introduced into polyvinylidene fluoride fibers prepared by electrospinning. The resulting changes in the structural, chemical and electrical properties of the samples were observed and compared using SEM-EDX, DSC, XPS, FTIR, Raman spectroscopy and electrical measurements. The observed results displayed a grouping of parameters by electronegativity and possibly the molecular mass of the additive salts. We virtually demonstrated elimination of the presence of the γ-phase by addition of Mg(NO3)2, Ca(NO3)2, and Zn(NO3)2 salts. The trend of electrical properties to follow the electronegativity of the nitrate salt cation is demonstrated. The performed measurements of nitrate salt inclusions into PVDF offer a new insight into effects of previously unstudied structures of PVDF composites, opening new potential possibilities of crystalline phase control of the composite and use in further research and component design.
Keywords: FTIR; PVDF; Raman spectroscopy; permittivity; XPS; XRD; nitrate salt; EDX